A follow-up survey of graduates at Faculty of Paramedical Sciences of Shahid Beheshti Medical University (1997-2000) done to apply its results in educational planning and guidance of aptitudes - Mousavijahed, Zahra; Saemian, Farah; Akbarzadeh Bagheban, Alireza (Archives of Advances in Biosciences, 2012)
The Higher National Council of Medical Sciences Planning (HNCMSP) in Iran compile and approve educational programs by using expert academic staff, considering the country,s needs and studying the background of establishment of each major in other countries. Since the employment of graduates in occupations related to their majors is of utmost importance in educational planning, this survey has been done to investigate the graduates, employment and the factors affecting it, using a retrospective study. This survey is done on 120 graduates of Laboratory Sciences (LS), Medical Records (MR) and Radiology Technology (RT), at Paramedical Faculty of Shahid Beheshti Medical University (1997-2000).The subjects were randomly selected and given a questionnaire and the data was statistically analyzed using one-way ANOVA,Chi-Square, and Exact Fisher’s test (SPSS 15). 63.5 percent of the samples were females and the rest were males with an average age of 35.The coordination between their aptitude and major was highest (61%) in LS graduates, but lowest (21%) in MR graduates. Also the coordination between majors and interest was highest in LS graduates (48.4%).The results indicate that 6% of the subjects were post graduate students, 91% were employed and 9% were jobless.75% of them believed that their jobs were quite related to their majors and interest. They also mentioned the same factors for finding a suitable job (P=0.328). The results show that there is a direct relationship between the students, interest and aptitude on one hand, and their major and interest on the other. Moreover, because of the coordination between the majors and the country’s needs, the rate of unemployment has been found to be very low(9%).These findings can be helpful in reevaluation of educational planning, guidance of aptitudes towards the country’s economic priorities, and having a study of post graduation status.